Terapi Non-Operatif Fraktur Maleolus Lateral pada Atlet Usia Remaja sebelum Return to Play - Laporan Kasus: Laporan Kasus - Feliciana, Anastasia; Laily, Inarota (Cermin Dunia Kedokteran, 2026)
Introduction: An ankle fracture is a discontinuity of the distal tibia or fibula involving the tibiotalar joint and is the most common fracture site in football. Most football-related fractures can be managed non-operatively; however, return-to-play (RTP) decisions should not be based on time alone. Case: A 17-year-old male football player sustained an incomplete right lateral malleolus fracture with preserved alignment after two inversion injuries. He was immobilized in a cast for two weeks, followed by non-weight bearing with crutches, and was referred to a sports medicine clinic for ankle stiffness and right calf atrophy. Reconditioning consisted of twice-daily non-weight bearing ankle mobility and strengthening exercises, followed by balance training and functional testing. After one week, active range of motion and calf size were clinically comparable between sides, although right single-leg balance remained inferior despite exceeding 45 seconds. At the subsequent evaluation, single-leg balance exceeded 60 seconds bilaterally and was symmetrical; squats and lunges were pain-free with good movement quality; and single-leg hop distance was symmetrical, although right-sided landing stability remained mildly impaired. Discussion: This article aims to review the principles and protocols of therapy, especially non-surgical therapy, for lateral malleolus fracture before the patient was finally allowed to RTP, and to compare their application in this case. Conclusion: Non-operative management followed by progressive reconditioning enabled this athlete to begin graded non-contact training. Full RTP should be deferred until full training is tolerated without pain or swelling and landing stability has recovered.